The Gotti Wars: taking down America's most notorious mobster - Gleeson, John (Scribner, 2022)
"A riveting, decades-in-the-writing memoir from the determined young prosecutor who, in two of America's most celebrated trials, managed to convict famed mob boss John Gotti--and subsequently took down the Mafia altogether."--Amazon